ISLAMIC HUMANISM IN INDONESIA'S CONTEXT: Discourse Analysis of Nationality Problems in Indonesia - Wahyudin Wahyudin; Agus Maimun; Mat Jalil (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
The thought of humanism originated in Athens. As a universal ideology, humanism is the foundation of modern civilization in the western and the eastern world. As an ideology, humanism is adopted by many third world countries, including Indonesia. Although there have been many discussions on Humanism, studies on Humanism in Islam perspective related to tolerance, freedom, and equality in Indonesia’s context have not been carried out. This study attempts to fill that gap including the values of tolerance, freedom, and equality of rights in Indonesia. It is conducted to discover the Islamic humanism developed in Indonesia. The results of the study are: (1) the Islamic humanism is very relevant in Indonesian context which has life philosophy of Pancasila; (2) tolerance as part of Islamic humanism still stands tall in Indonesia because people assume that it has high enthusiasm for safeguarding human dignity; (3) freedom of society in religion, expressing opinion, politics, and other national and state life activities has been guaranteed by the law, although there are still some restrictions by the government on freedom of society; (4) equality rights wise, there are still some Indonesian people who still get unfair law treatment, for example many low-economic level citizens who steal trivial items get severe penalties, while the corruptors stealing bigger amount of money often roam freely without supervision.